Fabrication and growth mechanism of t-selenium nanorods during laser ablation and fragmentation in organic liquids - Baimler, Ilya V.; Simakin, Alexander V.; Dikovskaya, Anastasia O.; Voronov, Valery V.; Uvarov, Oleg V.; Smirnov, Alexander A.; Sibirev, Alexey V.; Dorokhov, Alexey S.; Gudkov, Sergey V. (Frontiers in Chemistry, 2024)
The process of formation of selenium nanoparticles of various shapes and structures during laser ablation and fragmentation in various liquids has been studied. It was found that laser ablation and subsequent laser fragmentation in some organic solvents, such as ethanol, propanol-2, isobutanol, polyethylene glycol and diethanolamine, forms the trigonal form of selenium in the form of elongated nanorods approximately 1 μm long and 200 nm thick, with a clearly defined crystal structure. On the other hand, the use of deionized water, acetone, glycerol, and benzene as solvents results in the formation of spherical amorphous nanoparticles with a diameter of 100 nm.